Prospects of Wind Turbines With Diffuser Augmented Configurations: Bibliographic and Patent Analysis - Aydar Kurmanov; Bulat Salykov; Ayap Kurmanov; Uralbay Khassenov (Journal of Applied Engineering and Technological Science (JAETS), 2026)
Diffuser-augmented wind turbines (DAWTs) are a promising wind-energy concept designed to enhance airflow through the rotor and improve energy capture, especially in low-wind and urban environments. This study evaluates the development prospects of DAWTs through an integrated bibliometric and patent analysis. Bibliographic records were retrieved from Scopus, and patent records were obtained from Google Patents for the period 2013–2023. After screening and eligibility assessment, 334 scientific publications and 401 patent families were included in the final analysis. The results show a sustained increase in research output, with China, the United States, and Japan emerging as leading contributors. Keyword co-occurrence analysis identified four dominant research clusters: aerodynamics and optimization, design and materials, urban and distributed systems, and noise and control. Patent activity peaked around 2020 and was concentrated in China, the United States, and Europe, indicating growing commercial interest. Although DAWTs can achieve rotor-area-normalized performance values above the classical Betz limit, such results should be interpreted within the specific fluid-dynamic framework of ducted systems. Overall, DAWTs demonstrate strong technical potential, but large-scale deployment remains constrained by structural complexity, cost, and limited field validation. Future progress depends on scalable design, field testing, and techno-economic assessment.